Flash cold sintering of Nb2O5: polarity and electrolyte effects. Issue 3 (3rd July 2021) - Dong, Jian; Kermani, Milad; Hu, Chunfeng; Grasso, Salvatore
ABSTRACT: We report on a novel consolidation technique based on the combination of a liquid (cold sintering) and electricity (flash sintering). The evolution of hydrogen from electrolysis of the solvent triggered the Flash Cold Sintering (FCS) event without need for external heating. Electrochemical effects became pronounced in the presence of acetic acid solution as the electrolyte had an increased conductivity compared to pure water. By adjusting the acetic acid molar concentration to 0.5 M and by inverting the polarity during FCS a 5 mm diameter 0.8 mm thick Nb2 O5 sample was evenly sintered up to 99% in 100 s at a temperature as low as 350°C. Conventional sintered counterparts achieved a 95% relative density when dwelled for 240 min at 1400°C. The inherent complexity of the proposed FCS approach resulted in enhanced densification and weakly translucent samples.